Haritaki Terminalia chebula Retz A Magic Bullet for Various Remedies - Maurya, Ran Vijai K S (International Journal of Pharmaceutical & Biological Archive, 2016)
Haritaki Terminalia chebula Retz A Magic Bullet for Various Remedies